Generation of iPSCs from Genetically Corrected Brca2 Hypomorphic Cells: Implications in Cell Reprogramming and Stem Cell Therapy. (13th January 2014) - Navarro, S.; Moleiro, V.; Molina-Estevez, F.J.; Lozano, M.L.; Chinchon, R.; Almarza, E.; Quintana-Bustamante, O.; Mostoslavsky, G.; Maetzig, T.; Galla, M.; Heinz, N.; Schiedlmeier, B.; et al.
Abstract : Fanconi anemia (FA) is a complex genetic disease associated with a defective DNA repair pathway known as the FA pathway. In contrast to many other FA proteins, BRCA2 participates downstream in this pathway and has a critical role in homology-directed recombination (HDR). In our current studies, we have observed an extremely low reprogramming efficiency in cells with a hypomorphic mutation in Brca2 ( Brca2 Δ 27/ Δ27 ), that was associated with increased apoptosis and defective generation of nuclear RAD51 foci during the reprogramming process. Gene complementation facilitated the generation of Brca2 Δ 27/ Δ27 induced pluripotent stem cells (iPSCs) with a disease-free FA phenotype. Karyotype analyses and comparative genome hybridization arrays of complemented Brca2 Δ 27/ Δ27 iPSCs showed, however, the presence of different genetic alterations in these cells, most of which were not evident in their parental Brca2 Δ 27/ Δ27 mouse embryonic fibroblasts. Gene-corrected Brca2 Δ 27/ Δ27 iPSCs could be differentiated in vitro toward the hematopoietic lineage, although with a more limited efficacy than WT iPSCs or mouse embryonic stem cells, and did not engraft in irradiated Brca2 Δ 27/ Δ27 recipients. Our results are consistent with previous studies proposing that HDR is critical for cell reprogramming and demonstrate that reprogramming defects characteristic of Brca2 mutant cells can be efficiently overcome by gene complementation. Finally, based on analysis of the phenotype, genetic stability, and hematopoietic differentiation potential of gene-corrected Brca2 Δ 27/ Δ 27 iPSCs, achievements and limitations in the application of current reprogramming approaches in hematopoietic stem cell therapy are also discussed. Stem Cells 2014;32:436–446